Self‐Assembly versus Stepwise Synthesis: Heterometal–Organic Frameworks Based on Metalloligands with Tunable Luminescence Properties. Issue 34 (12th July 2013) - Zhang, Shu‐Ran; Du, Dong‐Ying; Tan, Ke; Qin, Jun‐Sheng; Dong, Hui‐Qing; Li, Shun‐Li; He, Wen‐Wen; Lan, Ya‐Qian; Shen, Ping; Su, Zhong‐Min
Abstract A new family of heterometal–organic frameworks has been prepared by two synthesis strategies, in which IFMC‐26 and IFMC‐27 are constructed by self‐assembly and IFMC‐28 is obtained by stepwise synthesis based on the metalloligand (IFMC=Institute of Functional Material Chemistry). IFMC‐26 is a (3, 6)‐connected net and IFMC‐27 is a (4, 8)‐connected 3D framework. The metalloligands Ni(H4L)(NO3)2 are connected by binuclear lanthanide clusters giving rise to a 2D sheet structure in IFMC‐28. Notably, IFMC‐26‐EuxTby and IFMC‐28‐EuxTby have been obtained by changing the molar ratios of raw materials. Owing to the porosity of IFMC‐26, Tb3+@IFMC‐26‐Eu and Eu3+@IFMC‐26‐Tb are obtained by postencapsulating TbIII and EuIII ions into the pores, respectively. Tunable luminescence in metal–organic frameworks is achieved by the two kinds of doping methods. In particular, the quantum yields of heterometal–organic frameworks are apparently enhanced by postencapsulation of LnIII ions.